Automated requirements-based generation of test cases for product families - Nebut, Clémentine; Pickin, Simon; Traon, Yves Le; Jézéquel, Jean-Marc (18th IEEE International Conference on Automated Software Engineering, 2003. Proceedings, 2003)
Software product families (PF) are becoming one of the key challenges of software engineering. Despite recent interest in this area, the extent to which the close relationship between PF and requirements engineering is exploited to guide the V&V tasks is still limited. In particular, PF processes generally lack support for generating test cases from requirements. In this paper, we propose a requirements-based approach to functional testing of product lines, based on a formal test generation tool. Here, we outline how product-specific test cases can be automatically generated from PF functional requirements expressed in UML. We study the efficiency of the generated test cases on a case study.